Collaboration between health sciences librarians and faculty as reflected by articles published in the Journal of the Medical Library Association. - Akers, Katherine G.; Higgins, Molly; DeVito, Jennifer A.; Stieglitz, Sally; Tolliver, Robert; Tran, Clara Y. (Journal of the Medical Library Association, 2018)
A recent study by Higgins and colleagues reports that the Journal of the Medical Library Association (JMLA) had the highest percentage of articles with both librarian and faculty coauthors out of 13 peer-reviewed journals in science, technology, engineering, and medicine librarianship and education between 2005 and 2014. A deeper and updated analysis of JMLA research articles and case studies published between 2008 and 2017 revealed that 29% of articles had both librarian and faculty coauthors. The main topics of librarianfaculty collaboration, as described in these articles, were related to patient and consumer health information and clinical information-seeking and decision-making by health care providers. Most faculty coauthors came from the disciplines of biomedical or health informatics and biostatistics and library and information science. The publication of these articles in the JMLA provides evidence of health sciences librarians' and information specialists' ability to collaborate with faculty members to advance the knowledgebase and practice of librarianship and the health sciences.